Deep Learning Approach in Toraja Culture-Based Mathematics Learning and its Effect on Primary Students’ Problem-Solving Skills - Yanti Lisa Lambe; Suri Toding Lembang; Ranak Lince (MATHEMA: JURNAL PENDIDIKAN MATEMATIKA, 2026)
This study aims to explore the Deep Learning approach in Toraja culture-based mathematics learning on the problem-solving skills of junior high school students. The research used an embedded sequential explanatory mixed methods design, with a quantitative approach as the primary method and a qualitative approach as supplementary. The subjects consisted of an experimental group and a control group. Quantitative data were collected through pre- and post-treatment essay tests and analyzed using ANCOVA, while qualitative data were obtained through interviews analyzed thematically. The results indicate that the Toraja culture-based Deep Learning approach had a significant effect on improving problem-solving skills (F(1,54)=48.206; p<.001) with a large effect size (ηₚ²=0.471). Qualitative data reinforce these findings by showing increased student engagement, reflection, and metacognitive awareness. The integration of Toraja culture into Deep Learning strengthens the meaning, relevance, and transfer of mathematical knowledge within students' socio-cultural context.